A Rare Case of Hypopharyngeal Screw Migration after Spine Stabilization with Plating - G. Salis; B. Pittore; G. Balata; C. Bozzo (Case Reports in Otolaryngology)
Anterior cervical spine fusion and stabilization with plating are well-established surgical procedures for the treatment of myelopathy, cervical spine traumas, and spinal infectious diseases. Various complications have been described in the literature, more frequently, intraoperative bleeding, peri- or postoperative hypopharyngeal, and/or esophageal ruptures with mediastinal deep infection and loosening and extrusion of the screws from the plating. Screw migration has also been observed as a complication of the procedure, either early in the postoperative period or delayed, even after many years. In some instances, the esophageal perforation can recover spontaneously with absence of complications, even if a case of plate failure and graft migration with lethal sudden airways obstruction has been reported. We describe a case of hypopharyngeal screw migration after cervical spine stabilization with plating never described before in the literature.